Editorial: The Future of Social Sciences - Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2017)
We have been facing with several challenges in all over the World. Global and local economies are facing threats as well as the increasing numbers of migrants that have not been seen for several decades. Resources are becoming scarcer and more expensive as we consume more. Technology and especially the internet and social networking are changing the way we work, interact and communicate. The question of